Determining the Independent Risk Factors and Mortality Rate of Nosocomial Infections in Pediatric Patients. (15th February 2016) - Aktar, Fesih; Tekin, Recep; Güneş, Ali; Ülgen, Cevat; Tan, İlhan; Ertuğrul, Sabahattin; Köşker, Muhammet; Balık, Hasan; Karabel, Duran; Yolbaş, Ilyas
Abstract : The objective of this study was to determine the rate, independent risk factors, and outcomes of healthcare-associated infections in pediatric patients. This study was performed between 2011 and 2014 in pediatric clinic and intensive care unit. 86 patients and 86 control subjects were included in the study. Of 86 patients with nosocomial infections (NIs), there were 100 NIs episodes and 90 culture growths. The median age was 32.0 months. The median duration of hospital stay of the patients was 30.0 days. The most frequent pathogens were Coagulase-negative Staphylococcus, Acinetobacter spp., Klebsiella spp., and Candida spp. Unconsciousness, prolonged hospitalization, transfusion, mechanical ventilation, use of central venous catheter, enteral feeding via a nasogastric tube, urinary catheter, and receiving carbapenems and glycopeptides were found to be significantly higher in NIs patients. Multivariate logistic regression analysis showed prolonged hospitalization, neutropenia, and use of central venous catheter and carbapenems as the independent risk factors for NIs. In the univariate analysis, unconsciousness, mechanical ventilation, enteral feeding, use of enteral feeding via a nasogastric tube, H2 receptor blockers, and port and urinary catheter were significantly associated with mortality. In the multiple logistic regression analysis, only mechanical ventilation was found as an independent predictor of mortality in patients with NIs.